Factors Influencing The Purchasing Decision of Eco-Friendly Shopping Bags: Green Awareness as an Intervening Variable - Sari, Puspa Novita (Journal of Applied Business Administration, 2023)
This study aims to analyze the factors influencing consumers' purchase of eco-friendly shopping bag products. The data obtained comes from 168 respondents, who are consumers that have previously purchased environmentally friendly shopping bags at Alfamart who lives at Solo Raya. Data measurement is conducted using the Structural Equation Model based on Partial Least Squares (PLS). The findings of the study suggest that green brand characteristics and green advertising play a role in shaping green awareness. Moreover, green awareness acts as a mediator between green brand attributes and purchasing choices, as well as between green advertising and purchasing choices. These research outcomes offer valuable insights for entrepreneurs to assess diverse factors impacting consumer purchasing behaviors, thereby potentially boosting company sales and profitability. This research contributes novelty by amalgamating a research model of factors influencing green awareness and green product purchasing decisions, wherein green awareness functions as an intervening variable.